The Effect of Debt to Equity Ratio (DER), Return on Asset (ROA), Liquidity, and Net Profit Margin (NPM) on Company Value - Meyske Yudit Hosio; Loggar Bhilawa (Jurnal Indonesia Sosial Teknologi, 2024)
The purpose of this study was to determine the effect of Debt to Equity Ratio (DER), Return On Asset (ROA), liquidity, and Net Profit Margin (NPM) on firm value in Real Estate and Property Companies listed on the Indonesia Stock Exchange in the period 2020-2022. The method used in this research is quantitative method. This study uses a sample research method totaling 34 companies selected using purposive sampling method with a total of 81 observation data free from outlier data. This study uses multiple linear regression analysis to test the effect of the independent variable on the dependent variable. The results of this study indicate that Debt to Equity Ratio (DER) has a significant positive effect on firm value, Return On Asset (ROA) has no effect on firm value, liquidity has no effect on firm value, and Net Profit Margin (NPM) has no effect on firm value.